EFEKTIVITAS PEMBEBASAN NARAPIDANA SAAT PANDEMI CORONA VIRUS DISEASE 2019 (Studi Kasus di Lapas Kelas I Kota Makassar) (Qawanin Jurnal Ilmu Hukum, 2021)
This research aims to determine how the effectiveness of assimilation and integration rights policies during the pandemic. Corona Virus and what factors hinder the assimilation and Integration Rights policy. So it can be concluded that the release of prisoners during the pandemic through assimilation and integration rights programs has not been effective, because there are still many prisoners who have received this policy but have returned to committing criminal acts, causing unrest in the community. In this study using the method of empirical law research type. This study also uses primary data and secondary data obtained through literature study (documents) and field studies as data collection techniques, then analyzed using qualitative analysis methods. The recommendation of this research is that the government must be able to make further actions or steps for safety and comfort for the community and prisoners so that there will be no problems and repetition of crimes during this pandemic and correctional institutions must provide motivation or encouragement to prisoners who have the ability / skills and skills. to assimilate so that what prisoners have can be useful for the prison, community, and individuals. Then the community should be more active and participate in supporting the assimilation program by accepting the presence of prisoners so that a sense of trust arises to provide opportunities to carry out assimilation and the right to integrate in the midst of society.